¿Cómo están cubriendo las elecciones los medios de comunicación? (2007)
ABSTRACT: The Electoral Observation Mission, MOE, today announces the first monitoring report to the media in this election period, a fundamental tool for determining the levels of visibility that the media are not only the different candidates in contention here, but the dynamics of the electoral process.